The Mediating Role of Investment Decision Making: The Impact of Financial Literacy, Mental Budgeting, Self Control on Financial Well-Being - Muhammad Ghiffary Ar Ridho Firdauz; Naelati Tubastuvi; Wida Purwidianti; Arini Hidayah (BASKARA : Journal of Business and Entrepreneurship, 2026)
This study aims to analyze the effect of financial literacy, mental budgeting, and self-control on financial well-being with investment decision making as a mediating variable. This study uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from a sample of 218 productive-age individuals who have invested in financial assets or real assets and reside on the island of Java. The results show that financial literacy have a positive and significant effect on financial well-being, while mental budgeting and self control do not show a significant direct on financial well-being. These findings indicate that there is evidence to support the mediator, namely investment decision making. This mediator mediates the relationship between the independent variables, namely financial literacy, mental budgeting, and self-control, and financial wellbeing. The results show that individuals with high financial literacy, good mental budgeting skills, and self-control tend to exhibit good investment decision-making behavior. As a result, this contributes to their overall financial wellbeing. In general, the theoretical implications of this study add to the existing knowledge, while the practical implications provide a useful perspective for policymakers, financial institutions, and individuals to promote their financial well-being.